Web Content Management System (WCMS): A Need (International Journal of Engineering and Computer Science, 2017)
The first thing that a visitor sees on a website is the content present on its web pages. It is generally difficult for many organisations to keep their web site content as up to date as per their requirement. Most of the time there are delays getting new content online. Due to the large volume of content and unwillingness to deal with the coding and other technicalities in the present-day context necessitates development and deployment of Content Management Systems. This research paper is aimed to justify that why so many organisations are turning to CMS for their website development